Novel expression patterns for trefoil peptides : presence of Tff2 and Tff3 in rodent cochlea - Lubka, Maria (Array, 2008)
Summary: Trefoil peptides: Tff1, Tff2 and Tff3, assigned to the so-called trefoil factor family (TFF), are secretory proteins predominantly expressed by the gastrointestinal (GI) epithelial cells. Their multiple protective functions include an important role in immune response and apoptosis. Here, a novel localization of Tff2 and Tff3 in the cochlea of mouse inner ear is presented. Tffs expression and localization in mouse cochlea was analyzed by using the quantitative real time PCR (qPCR) and immunohistochemistry. Tff2 and Tff3 mRNA quantification by qPCR showed their presence in the cochlea. Immunohistochemistry demonstrated the presence of Tff2 in the spiral ligament and limbus and for Tff3 in the spiral ligament and the organ of Corti. These new and surprising findings of Tff's presence in the cochlea indicate a new role of TFFs connected with the organ of hearing which still needs to be physiologically evaluated